Knowledge, Attitude, and Practice of Infection Control and Waste Management among Traditional Medicine Practitioners in Bhutan, 2019: A Nationwide Cross-Sectional Survey. (12th April 2021) - Gyeltshen, Dorji; Dorji, Thinley; Choda, Sonam; Gyeltshen, Chencho; Dorji, Sangay; Dorji, Tashi; Tshering, Ugyen; Wangmo, Diki; Pongpirul, Krit
Abstract : Background . In Bhutan, Traditional Medicine (TM) is a part of the government-sponsored free healthcare system and Traditional Medicine Units (TMUs) are colocated with allopathic hospitals. Prevention of healthcare-associated infections and patient safety must apply to all institutionalized healthcare settings including TMUs. This study assessed the knowledge, attitude, and practice of TM practitioners in Bhutan in the field of infection control and waste management practices. Methods . This was a descriptive study among TM practitioners selected through simple random sampling. Data were collected using a structured pro forma and entered in EpiData 3.1 and analyzed in STATA 13.1. Results . There were 132 respondents (response rate 98%). The majority (64%) knew the seven steps of handwashing but their knowledge of WHO's Five Moments for Handwashing was poor, especially handwashing after aseptic procedures (17%) and handwashing after touching patient surroundings (5%). Handwashing before palpation of the pulse (37%) and using gloves while dispensing medicines (9%) were poor; but the proportions of handwashing before performing moxibustion (96%), correct disposal of sharps (84%), and disinfection of cupping sets (78%) were high. The majority of participants hold a positive attitude towards the adoption of infection control and waste management practices for the benefit of patients. Only 23% had received preservice and 44% had received in-service training on infection control. Conclusions . The knowledge and practices of infection control and waste management are optimal only in select domains of practice. The practitioners hold a positive attitude towards the adoption of infection control and waste management standards.